Production of the English Voiceless Labiodental Fricative /f/ by Sundanese EFL Student Teachers: A Case Study - Aisyah Hamidiyah; Bambang Kaswanti Purwo; Faizah Sari (Journal La Edusci, 2026)
The production of English consonants can be challenging for EFL learners, particularly when the target sounds are absent or have limited use in their first language. This study investigated the production and substitution patterns of the English voiceless labiodental fricative /f/ among Sundanese EFL student teachers in Banten. A qualitative case study design supported by descriptive frequency analysis was employed. The participants were 12 undergraduate English Education students aged 20–21 years who regularly used Sundanese in daily communication and had completed pronunciation and phonetics courses. Data were collected through two oral-reading recording sessions using 30 isolated words and 22 sentences containing English labiodental fricatives. The analysis focused on 78 occurrences of /f/ in initial, medial, and final word positions. The recordings were transcribed using the International Phonetic Alphabet, classified according to their phonetic realizations and phonological environments, and validated by two expert raters. The findings showed that /f/ was substituted with the voiceless bilabial stop [p], voiced labiodental fricative [v], voiced velar stop [g], and voiceless velar stop [k]. The substitution of /f/ with [p] was the most frequently identified pattern. These substitutions occurred across different word positions and were influenced by surrounding sounds and orthographic forms, particularly words containing <ph> and <gh>. The findings highlight the need for explicit pronunciation instruction focusing on articulatory features, phonological environments, and English sound–spelling relationships.